Odpowiedzi

  • Roma
  • Community Manager
2010-01-10T00:58:21+01:00
Równanie prostej przechodzącej przez dwa punkty A = (x₁, y₁) i B = (x₂, y₂) ma postać: (x₂ - x₁)(y - y₁) = (y₂ - y₁)(x - x₁)

a) A=(1,2) B=(-1,-4)
(-1 - 1)(y - 2) = (-4 - 2)(x - 1)
-2(y - 2) = -6(x - 1)
-2y + 4 = -6x + 6
-2y = -6x +6 - 4
-2y = -6x +2 /:(-2)
y = 3x - 1

b) A=(1,1) B=(-1,5)
(-1 - 1)(y - 1) = (5 - 1)(x - 1)
-2(y - 1) = 4(x - 1)
-2y + 2 = 4x - 4
-2y = 4x -4 -2
-2y = 4x - 6 /:(-2)
y = -2x + 3

c) A=(4,-2) B=(12,0)
(12 - 4)(y + 2) = (0 + 2)(x - 4)
8(y + 2) = 2(x - 4)
8y + 16 = 2x - 8
8y = 2x - 8 - 16
8y = 2x - 24 /:8
y = ¼x - 3

d) A=(2,-3/4) B=(-3/2, 1)
(-1,5 - 2)(y + ¾) = (1 + ¾)(x - 2)
-3,5(y + 0,75) = 1,75(x - 2)
-3,5y - 2,625 = 1,75x - 3,5
-3,5y = 1,75x - 3,5 +2,625
-3,5x = 1,75x - 0,875 /:(-3,5)
y = - 0,5x + 0,25
y = -½x + ¼